Platform Digital and Content Innovation to Increase Youth Interest in the Agricultural Sector - Mambang M; Finki Dona Marleny (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2022)
The use of digital technology is essential in increasing the younger generation's interest in the agricultural sector. Deficient awareness of youth in the agricultural sector, even though the agricultural sector has great potential and has a crucial role in handling anything. The methodology carried out in this study uses data collection, initial processing of data, analysis using python, evaluation, and validation of results. Content with agricultural topics, the use of the Internet of things on agriculture that contains the content of the role of the younger generation in the agricultural sector is then used as a dataset. Variables analyzed in these contents include the year of content creation, how many subscribers, number of viewers, and number of videos. In-person interviews with the younger generation were also conducted to explore information with variables in knowledge levels, family environment factors, land availability, social practice, risk factors, and income. The results and discussions of the analysis of content related to agriculture and the Internet of things showed the younger generation's interest in farming with the help of digital platforms. Of the 30 respondents used as a sample, prestige social has the highest value compared to other variables with 0,59. The results obtained from the analysis showed that the number of impressions on content related to the younger generation in the agricultural sector reached 248,882,953 impressions, and the number of impressions related to the Internet of Things content was as many as 23. 969 impressions. The use of technology with the digital Youtube platform is an excellent opportunity to give birth to various kinds of innovations by utilizing digital technology to support the sustainability of the agricultural sector in Indonesia.